2024
DOI: 10.1021/acs.analchem.3c05108
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Biosensing Based on Bifurcated DNA Scaffold-Aggregated Ag Nanocluster via Responsive Conformation Switch of Quasi-Molecular Beacon

Jiayang He,
Xin Shang,
Min Long
et al.

Abstract: To address the limitations of typical hairpinstructural molecular beacons, exploring the ability of a quasimolecular beacon (qMB) to create label-free fluorescence biosensors is intriguing and remains a challenge. Herein, we propose the first example of modular qMB with the feature of a stimulation-responsive conformation switch to develop an aggregated Ag nanocluster (aAgNC) in a bifurcated DNA scaffold for fluorescently sensing a specific initiator (I*). This qMB was well designed to program four functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Six DNA strands (DNA1–DNA6) were designed to incorporate a template region for synthesizing AgNCs at the 5′ terminus along with A4-linker (-AAAA) at the 3′ terminus for further aptamer coupling (Table ). These template regions were tailored based on well-established DNA templates for AgNCs-DNA synthesis. On the other hand, the aptamer strands were specifically designed to incorporate the aptamer along with T4-linker (-TTTT) at the 3′ terminus (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Six DNA strands (DNA1–DNA6) were designed to incorporate a template region for synthesizing AgNCs at the 5′ terminus along with A4-linker (-AAAA) at the 3′ terminus for further aptamer coupling (Table ). These template regions were tailored based on well-established DNA templates for AgNCs-DNA synthesis. On the other hand, the aptamer strands were specifically designed to incorporate the aptamer along with T4-linker (-TTTT) at the 3′ terminus (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…More interestingly, varying the length, base sequence, or structure and conformation of DNA can precisely modulate the physical properties and fluorescence response of DNA–Ag NCs. For instance, Shah et al reported that hairpin-structured DNA templates with a six-base cytosine loop (6C loop) are responsible for the strong emission of Ag NCs. However, the fluorescence of Ag NCs is reduced due to disruption of the probe’s hairpin structure upon target miRNA hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence-specific DNA-templated Ag clusters are formed through coordinating of silvers with short, single-stranded nucleobases. The resulting DNA-cluster adducts, showing long-term stability, tunable spectral performance, and good biocompatibility, serve as increasingly attractive fluorophores for biosensing and imaging. , Building on these advantages, some interesting studies further explored the spectral and photophysical fluorescent profiles of Ag clusters that were synthesized in bifurcated parent scaffolds with two-split contiguous single-stranded oligonucleotides . When two split fragments were forced together on a short DNA duplex by a guided hybridization assembly, this DNA-Ag cluster complex was found to favor locally higher DNA concentrations and preferentially develop.…”
Section: Introductionmentioning
confidence: 99%
“…These achievements provided great possibilities and opportunities to program Ag-clustering templates at tailored domains in different DNA structures, especially those tethering with multiple functional sites, leading to the creation of two-stranded fluorescence complementation biosensors with high specificity and on–off contrast. By separating the cluster parent template in two splits and exquisite programming, various split-DNA hosting constructs, such as functional three-way-junction architecture, repetitive nicks cascaded in hybridization chain reaction products, or a simple modular quasi-molecular beacon with controllable conformation switch, were also assembled in our group to form fluorescent Ag cluster unites, and their unique spectral behavior and stable fluorescent features were demonstrated for developing label-free fluorescence assay platforms. Thus, encouraged by this progress, it would be desirable to create multiple Ag clusters with a cooperatively enhanced effect in a 2D DNA nanoring for amplification-free biosensing applications.…”
Section: Introductionmentioning
confidence: 99%